Предмет: Алгебра,
автор: Ludmila201
Упростите выражение :( -6a+ab-(-ab+a)
Ответы
Автор ответа:
0
-7а + 2аб вот как то так
Автор ответа:
0
ab/a+b·(a/b-b/a)=ab/a+b·(a²-b²/ab)=ab/a+b·(a+b)(a-b)/ab=a-b=
=√3-1-(√3+1)=√3-1-√3-1=-2
Ответ: -2
=√3-1-(√3+1)=√3-1-√3-1=-2
Ответ: -2
Автор ответа:
0
Упростите выражение 6a (a – х + c) + 6х (a + х – c) – 6c (a – х – c).
Похожие вопросы
Предмет: Русский язык,
автор: aishakolbasa201108
Предмет: Математика,
автор: ilyasik0604
Предмет: Математика,
автор: SergeyWl
Предмет: Математика,
автор: Aleexandra
Предмет: Алгебра,
автор: Аноним